Corporate Social Responsibility Practices in Islamic Financial Institutions: The Difference between an Islamic Bank and a Socially Responsible Bank - Hamou, Nadia; Mebarki, Hanene (جامعة الشهيد حمه لخضر الوادي - كلية العلوم الاقتصادية والتجارية وعلوم التسيير - مخبر اقتصاديات الطاقات المتجددة ودورها في تحقيق التنمية المستدامة, 2022)
The objective of this article is to make an empirical comparison between Islamic finance and Corporate Social Responsibility through a comparison of practices of two private banks active in Algeria,one that is an Islamic bank and the other which is a classical bank that is known for its social commitment. To this end, we opted for a documentary study with the aim of analysing the content and quality of the information contained in the annual activity reports of the two banks selected. The data was processed using the qualitative analysis software Nvivo. The results obtained showed that the behaviour of the two banks is almost similar, they take into consideration all CSR‟s dimensions with more or less significant proportions, Each bank gives a particular interest to one dimension in spite of the others.
Keywords: المصارف الإسلامية -- القطاع المصرفي -- التمويل الإسلامي -- المسؤولية الاجتماعية